Representing political attitudes through recontextualizing the metaphor ‘Shuai Guo’ in English-translated Chinese diplomatic discourse - Yang, Wei; Syed Abdullah, Syed Nurulakla; Ang, Lay Hoon; Yang, Mingxing (Cogent OA, 2025)
Diplomatic discourse has garnered a share of scholarly attention in translation studies, albeit the recontextualization of its metaphoric expression has remained underexplored across languages. This present study delved into the Chinese metaphor 甩锅 (‘shuai guo’, literally means ‘throw the wok’) as a case, aiming to examine how the metaphor was recontextualized in the new context to implicate diplomatic attitudes. The data for analysis were drawn from China’s Foreign Ministry spokespersons’ remarks at regular press conferences spanning from 2020 to 2022. Utilizing a qualitative descriptive approach, this research scrutinized the patterns and forms of its English translations. Drawing upon Fairclough’s framework of recontextualization, this study discussed how the metaphors were recontextualized from aspects of absence, abstraction, addition, and arrangement. It was found that the English translations of ‘shuai guo’ predominantly revolved around blame-centered expressions, among other variations. The translations exhibited dynamic shifts in response to different contexts, shedding light on the discursive strategies to convey political attitudes towards the involved parties in the remarks, thereby aligning with the official ideologies. This study underscores the significance of the recontextualization process in translating metaphor in diplomatic discourse across languages, which may not be materialized by only focusing on the original text.